Pulmonary rehabilitation in COVID-19 pneumonia sequelae: so near yet so far - Hussain, Aqeel (ERJ Open Res, 2021)
To evaluate the benefit of pulmonary rehabilitation, a control group is a must to mitigate the effect of confounding factors like spontaneous resolution of lung damage, learning effect and better mental status https://bit.ly/3qy5sfe